Phonological and Speech Motor Abilities in Children with Childhood Apraxia of Speech and Phonological Disorder - Lewis, Anne Marie (Curtin University, 2018)
This thesis investigated whether childhood apraxia of speech (CAS) differs from phonological disorder (PD) regarding their causal origin. After developing and validating measures targeting components of phonology and speech motor control, we explored if speech motor ability constrained phonological development in CAS more than in PD. This thesis demonstrated children with CAS show a distinct profile of speech impairments but little evidence that their motor deficit constrains phonological development in a way distinct from PD.